Preservation Value of Vernacular Architecture in Kuta Village: Exploring Its Unique Characteristic - Hani Nurhidayanti; Hanson E. Kusuma (Talenta Publisher, 2025)
Presently, numerous traditional villages across various regions are undergoing a series of changes and modifications. Among these changes is the unavoidable influence of globalization. This phenomenon, if unaddressed, poses a significant threat to the distinctive characteristics and uniqueness of vernacular architecture. A case study of Kampung Kuta in Ciamis Regency, Indonesia, illustrates these phenomena. The integration of contemporary elements, including forms, materials, and construction methods, is evident in several new buildings in Kampung Kuta. This research aims to clarify the unique characteristics of the vernacular architecture in the old buildings of Kampung Kuta and evaluate their preservation value based on community perceptions. The study was conducted in two stages. The initial stage utilized an exploratory qualitative approach, incorporating a questionnaire survey with open-ended questions, along with documentation of Kampung Kuta, to identify the unique variables of vernacular architectural character and its preservation significance. The second stage of the research was conducted in an explanatory quantitative manner through a survey using a closed questionnaire. This questionnaire was prepared based on the results of the previous qualitative data analysis. The collected data were analyzed using factor analysis and regression to identify the relationship between the uniqueness of Kuta Village's vernacular architecture and its preservation value. The results of the analysis were mapped using the conceptual framework of cultural significance in preservation. The analysis yielded five distinct character groups in old buildings in Kuta Village: traditional identity, building beauty, cultural heritage, response to natural context, and sacredness. Of these, three groups customary identity, creating beauty, and response to natural context,exerted a significant influence on the value of preservation. This research aims to support the preservation of vernacular architecture in traditional villages, particularly in Kuta Village. Keyword: Vernacular Architecture, Kuta Village, Characteristic, Preservation